Assets Growth and Common Stock Returns - Poudel, Shiva Raj (Journal of Nepalese Business Studies, 2025)
The primary aim of the study is to assess how changes in the firm assets influence the variation in expected stock returns. Total assets growth only captures the aggregate growth of the firm. It does not deal whether expansion across different asset categories is likewise consistently linked to the common stock returns. Therefore, total assets growth has been decomposed in to liquid assets growth, current assets growth other than liquid assets, property plant and equipment growth, and other assets growth. The study is based on secondary dataset. All the data relating to stock prices to calculate capital gain yield were obtained form the NEPSE database for all samples firms. All the data for assets growth parameters were obtained from financial reports of concern firms. Hence, A balanced panel dataset was compiled from 48 firms over 12 years covering 2010/11 to 2021/22 resulting in 576 observations. Data analysis tools include descriptive statistics, correlation analysis, and regressions analysis. The results reveal that the higher the total assets growth, the greater the equity returns in Nepali capital market. In addition, assets decomposition analysis confirmed that only the other assets growth has the significant positive impact on common stock returns for all samples firms, BFIs, and insurance companies. Hence, policymakers and investors in Nepali capital market should carefully evaluate assets growth when making investment choices.